Analysis of Psychological Conditions and Cognitive Load after Aircraft Accident/Incident on Air Traffic Controller Situational Awareness - Erwin Munda; Nunuk Praptiningsih; Rahmawati Sukra; Dhian Supardam; Aldela Ayu Titi Nurhawani (Asian Journal of Applied Education (AJAE), 2026)
This study analyzes the effect of psychological conditions and cognitive load after aircraft accident/incident on situational awareness among Air Traffic Controllers at AirNav Indonesia Surabaya Branch. Using a quantitative survey design, data were collected from 60 respondents through Likert-scale questionnaires and analyzed using validity, reliability, correlation, classical assumption, multiple regression, t-test, F-test, and determination coefficient procedures. The results show that psychological conditions and cognitive load were moderate, while situational awareness was high. Both variables had no significant partial or simultaneous effect on situational awareness. These findings indicate that controller situational awareness may be more strongly shaped by experience, training, procedures, technology, organizational support, and safety culture.